Making biocontrol options more accessible to African farmers-Aflasafe - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2011)
In this interview, Dr. Peter Cotty, A Research Plant Pathologist with Agricultural Research Service, USDA Department of Plant Sciences University of Arizona spoke extensively on his partnership with IITA scientists on the impact of Biocontrol options for African farmers most importantly the newly developed product, aflasafe.